Translation Strategies in You'll be in My Heart Song Lyrics Niki Version on Indolirik YouTube Channel - Meriska Yosiana (Asosiasi Dosen Muda Indonesia, 2025)
Translation has an important role in this modern era, it can help the readers or audiences from different countries understand about the meanings that want to be delivered. The purpose of this research is to analyze the translation strategies in You’ll be in my Heart Song lyrics from English into Indonesian that is on Indolirik YouTube channel. You’ll be in my heart is very popular song and it became the original soundtrack of Tarzan movie in 1999. The song has reached more famous after it is being sung by Niki for Sportify Singles. The aim of this research is to find out the translation strategies in You’ll be in My Heart song lyrics on Indolirik YouTube Channel. The researcher used descriptive qualitative as a research method to analyze the data. This research used translation strategies from Gorlee (2005). There are 4 song verses in this song lyrics that are transcribed into 55 lines of lyrics. The result of this research shows that there are 6 strategies of 7 strategies used, namely paraphrasing 27 data, specification 3 data, neutralization 3 data, information reduction 9 data, functional reinterpretation 1 datum, explication 12 data, and no data for formatting. The most strategy used is paraphrasing for You’ll be in My Heart song lyrics by Niki version on Indolirik YouTube channel.